Selagibenzophenone B and Its Derivatives: SelB-1, a Dual Topoisomerase I/II Inhibitor Identified through In Vitro and In Silico Analyses - Donmez, Serhat; Lapinskaite, Ringaile; Atalay, Hazal Nazlican; Tokay, Esra; Kockar, Feray; Rycek, Lukas; Ozbil, Mehmet (Amer Chemical Soc, 2024)
The development of multitargeted drugs represents an innovative approach to cancer treatment, aiming to enhance drug effectiveness while minimizing side effects. Herein, we sought to elucidate the inhibitory effect of selagibenzophenone B derivatives on the survival of cancer cells and dual topoisomerase I/II enzyme activity. Results demonstrated that among the compounds, SelB-1 selectively inhibited the proliferation and migration of prostate cancer cells while exhibiting minimal effects on healthy cells. Furthermore, SelB-1 showed a dual inhibitory effect on topoisomerases. Computational analyses mirrored the results from enzyme inhibition assays, demonstrating the compound's strong binding affinity to the catalytic sites of the topoisomerases. To our surprise, SelB-1 did not induce apoptosis in prostate cancer cells; instead, it induced autophagic gene expression and lipid peroxidation while reducing GSH levels, which might be associated with ferroptotic death mechanisms. To summarize, the findings suggest that SelB-1 possesses the potential to serve as a dual topoisomerase inhibitor and can be further developed as a promising candidate for prostate cancer treatment.
Keywords: cancer; dual inhibition; in silico moleculardocking; in vitro; topoisomerase